Self-Organizing Systems 4th IFIP TC 6 International Workshop, IWSOS 2009, Zurich, Switzerland, December 9-11, 2009. Proceedings - Spyropoulos, Thrasyvoulos.; Hummel, Karin Anna. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 4th International Workshop on Self-Organizing Systems, IWSOS 2009, held in Zurich, Switzerland, in December 2009. The 14 revised full papers and 13 revised short papers presented were carefully selected from the 34 full and 27 short paper submissions. The papers are organized in topical sections on ad hoc and sensor networks; services, storage, and internet routing; peer-to-peer systems; theory and general approaches; overlay networks; peer-to-peer systems and internet routing; wireless networks; and network topics.